2017
DOI: 10.1002/pmic.201600350
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin specific peptidase 5 mediates Histidine‐rich protein Hpn induced cell apoptosis in hepatocellular carcinoma through P14‐P53 signaling

Abstract: Hpn is a small histidine-rich cytoplasmic protein from Helicobacter pylori and has been recognized as a high-risk factor for several cancers including gastric cancer, colorectal cancer, and MALT lymphoma. However, the relationship between Hpn and cancers remains elusive. In this study, we discovered that Hpn protein effectively suppressed cell growth and induced apoptosis in hepatocellular carcinoma (HCC). A two-dimensional gel electrophoresis and mass spectrometry-based comparative proteomics was performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Also, USP22 is responsible for hepatocellular carcinoma migration 19 . USP5 has been reported in targeting several proteins, such as P53, FOXM1, SLUG, βcatenin, c-Maf, TUFM, HDAC2 et al 4 - 9 , 20 , 21 . USP5 has also been implicated in a wide variety of cellular events, such as the efficient repair of DNA Double-Strand Breaks, alternative RNA Splicing, neural pain, tumor cell proliferation and progression 6 , 9 , 15 , 16 , 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, USP22 is responsible for hepatocellular carcinoma migration 19 . USP5 has been reported in targeting several proteins, such as P53, FOXM1, SLUG, βcatenin, c-Maf, TUFM, HDAC2 et al 4 - 9 , 20 , 21 . USP5 has also been implicated in a wide variety of cellular events, such as the efficient repair of DNA Double-Strand Breaks, alternative RNA Splicing, neural pain, tumor cell proliferation and progression 6 , 9 , 15 , 16 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…USP5 has also been implicated in a wide variety of cellular events, such as the efficient repair of DNA Double-Strand Breaks, alternative RNA Splicing, neural pain, tumor cell proliferation and progression 6 , 9 , 15 , 16 , 22 . Intriguingly, USP5 has been confirmed to mediate p53 signaling 20 , wnt-β-catenin pathway 5 , Type I interferon signaling pathway 23 , Notch and RTK signaling pathway 24 . A recent study confirmed that upregulated USP5 can promote pancreatic cancer 10 .…”
Section: Discussionmentioning
confidence: 99%
“…USP5 has been associated with tumorigenesis [15][16][17][18][19] , neurodegeneration [20][21][22] , and viral infections 23,24 . In addition, USP5 plays a role in regulation of ubiquitin levels in DNA damage repair 25 and stress granules 26 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been previously reported that IMPDH2 was the predominant isoform in neoplastic and replicating cells (5). Accumulating evidence has also suggested that IMPDH2 may be closely implicated in different types of malignancy (18)(19)(20)(21). In addition, it was revealed that IMPDH2 may be a useful biomarker for patient prognosis (20,21).…”
Section: Discussionmentioning
confidence: 99%